Training load and injury incidence over one season in adolescent Arab table tennis players: A pilot study - Pullinger, S. A.; Rejeb, A.; Varamenti, E.; Cardinale, M. (Asian Journal of Sports Medicine, 2019)
Background: It has been established that injury incidence data and training load in table tennis is somewhat limited.